Workplace analysis and design using virtual reality techniques. Issue 1 (2018) - Michalos, George; Karvouniari, Anna; Dimitropoulos, Nikolaos; Togias, Theodoros; Makris, Sotiris
Abstract: Workplace layout affects worker wellbeing and is linked to productivity, physical fatigue and production costs. So far, workplace optimization is based on observational methods and software simulations which may not be insightful, while full size prototypes signify high costs and implementation time. This work proposes a method to analyse and enhance industrial workplaces using immersive virtual reality. The system allows the tracking of multiple users virtually performing assembly tasks inside a CAVE system and the visualization of KPIs (e.g. completion time, traveled distance, ergonomics) for supporting decision making by production engineers. A case study is used to demonstrate the approach.